Qualitative Analysis of the Influence of Job Description, Human Capital, and Work Culture on the Performance of Employees of the Langsa Kota Sub-district Office - Siregar, Zulfirman; Simamora, Roy Sander; Tarigan, Rini Meylani; Nurmawati, Nurmawati; Rifai, Muhammad; Rahayu, Sri (Mahesa Research Center, 2025)
This study aims to analyze the influence of job description, human capital, and work culture on employee performance at the Langsa Kota Sub-district Office. A qualitative approach is used with a case study method, involving in-depth interviews, participatory observation, and document analysis as data collection techniques. The research informants consisted of the head of the office, administrative staff, and functional employees who were selected purposively. The results of the study show that a clear job description plays an important role in providing job guidance to employees. However, some challenges were found, such as unclear tasks in certain positions and overlapping responsibilities between employees, which could affect work coordination. From the aspect of human capital, formal education, technical training, and work experience have proven to have a great contribution to the quality of employee performance. However, limited access to training and competency development is a major obstacle, especially for new employees. Meanwhile, the work culture at the Langsa Kota Sub-district Office is generally considered positive, especially in the aspect of team cohesion. However, the discipline and innovation aspects still need more attention to encourage productivity and creativity at work. These three factors, namely job description, human capital, and work culture, are interrelated and affect employee performance simultaneously. This study concludes that optimal human resource management must include evaluation of task descriptions, improvement of training programs, and strengthening work culture. The implications of this study are expected to be a reference for the Langsa Kota Sub-district Office to improve employee performance in providing more effective and efficient public services.